The association of geriatric syndromes with hospital outcomes - Romero-Ortuno, Roman (My University, 2017)
BACKGROUND: Frailty, history of dementia (HoD), and acute confusional states (ACS) are common in older patients admitted to hospital. OBJECTIVE: To study the association of frailty (≥6 points in the Clinical Frailty Scale [CFS]), HoD, and ACS with hospital outcomes, controlling for age, gender, acute illness severity (measured by a Modified Early Warning Score in the emergency department), comorbidity (Charlson Comorbidity Index), and discharging specialty (general medicine, geriatric medicine, surgery). DESIGN: Retrospective observational study. SETTING: Large university hospital in England. PATIENTS: We analyzed 8202 first nonelective inpatient episodes of people aged 75 years and older between October 2014 and October 2015. MEASUREMENTS: The outcomes studied were prolonged length of stay (LOS ≥10 days), inpatient mortality, delayed discharge, institutionalization, and 30-day readmission. Statistical analyses were based on multivariate regression models. RESULTS: Independently of controlling variables, prolonged LOS was predicted by CFS ≥ 6: odds ratio (OR) =1.55; 95% confidence interval [CI], 1.36-1.77; P < 0.001; HoD: OR = 2.16; 95% CI, 1.79-2.61; P < 0.001; and ACS: OR = 3.31; 95% CI, 2.64-4.15; P < 0.001. Inpatient mortality was predicted by CFS ≥6: OR = 2.29; 95% CI, 1.79-2.94; P < 0.001. Delayed discharge was predicted by CFS ≥6: OR = 1.46; 95% CI, 1.27-1.67; P < 0.001; HoD: OR = 2.17; 95% CI, 1.80-2.62; P < 0.001; and ACS: OR = 2.29; 95% CI: 1.83-2.85; P < 0.001. Institutionalization was predicted by CFS ≥6: OR = 2.56; 95% CI, 2.09-3.14; P < 0.001; HoD: OR = 2.51; 95% CI, 2.00-3.14; P < 0.001; and ACS: OR 1.93; 95% CI, 1.46-2.56; P < 0.001. Readmission was predicted by ACS: OR = 1.36; 95% CI, 1.09-1.71; P = 0.006. CONCLUSIONS: Routine screening for frailty, HoD, and ACS in hospitals may aid the development of acute care pathways for older adults
PUBLISHED
Keywords: older adults; Frailty; acute confusional states (ACS); older adults; Frailty; acute confusional states (ACS); Ageing